Project20: maternity care mechanisms that improve access and engagement for women with social risk factors in the UK – a mixed-methods, realist evaluation. Issue 2 (7th February 2023) - Rayment-Jones, Hannah; Dalrymple, Kathryn; Harris, James M; Harden, Angela; Parslow, Elidh; Georgi, Thomas; Sandall, Jane
Abstract : Objectives: To evaluate how women access and engage with different models of maternity care, whether specialist models improve access and engagement for women with social risk factors, and if so, how? Design: Realist evaluation. Setting: Two UK maternity service providers. Participants: Women accessing maternity services in 2019 (n=1020). Methods: Prospective observational cohort with multinomial regression analysis to compare measures of access and engagement between models and place of antenatal care. Realist informed, longitudinal interviews with women accessing specialist models of care were analysed to identify mechanisms. Main outcome measures: Measures of access and engagement, healthcare-seeking experiences. Results: The number of social risk factors women were experiencing increased with deprivation score, with the most deprived more likely to receive a specialist model that provided continuity of care. Women attending hospital-based antenatal care were more likely to access maternity care late (risk ratio (RR) 2.51, 95% CI 1.33 to 4.70), less likely to have the recommended number of antenatal appointments (RR 0.61, 95% CI 0.38 to 0.99) and more likely to have over 15 appointments (RR 4.90, 95% CI 2.50 to 9.61) compared with community-based care. Women accessing standard care (RR 0.02, 95% CI 0.00 to 0.11) and black women (RR 0.02, 95% CI 0.00 to 0.11) were less likely to have appointments with a known healthcare professional compared with the specialist model. Qualitative data revealed mechanisms for improved access and engagement including self-referral, relational continuity with a small team of midwives, flexibility and situating services within deprived community settings. Conclusion: Inequalities in access and engagement with maternity care appears to have been mitigated by the community-based specialist model that provided continuity of care. The findings enabled the refinement of a realist programme theory to inform those developing maternity services in line with current policy.